Genome-Wide Characterization Analysis of CCT Genes in Raphanus sativus and Their Potential Role in Flowering and Abiotic Stress Response - Qunyun Tan; Zhengjin He; Shiyong Mei; Jifang Zhang (Horticulturae, 2022)
CCT genes play vital roles in flowering, plant growth, development, and response to abiotic stresses. Although they have been reported in many plants, the characterization and expression pattern of CCT genes is still limited in R. sativus. In this study, a total of 58 CCT genes were identified in R. sativus. Phylogenetic tree, gene structure, and conserved domains revealed that all CCT genes were classified into three groups: COL, CMF, and PRR. Genome-wide identification and evolutionary analysis showed that segmental duplication expanded the CCT gene families considerably, with the LF subgenome retaining more CCT genes. We observed strong purifying selection pressure for CCT genes. RsCCT genes showed tissue specificity, and some genes (such as RsCCT22, RsCCT36, RsCCT42 and RsCCT51) were highly expressed in flowers. Promoter cis-elements and RNA-seq data analysis showed that RsCCT genes could play roles in controlling flowering through the photoperiodic pathway and vernalization pathway. The expression profiles of RsCCT genes under Cd, Cr, Pb, and heat and salt stresses revealed that many RsCCT genes could respond to one or more abiotic stresses. Our findings could provide essential information for further studies on the function of RsCCT genes.